2013
DOI: 10.1128/jb.02104-12
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Clostridium difficile Spore Coat Proteins

Abstract: dSpores of Clostridium difficile play a key role in the dissemination of this important human pathogen, and until recently little has been known of their functional characteristics. Genes encoding six spore coat proteins (cotA, cotB, cotCB, cotD, cotE, and sodA) were disrupted by ClosTron insertional mutagenesis. Mutation of one gene, cotA, presented a major structural defect in spore assembly, with a clear misassembly of the outermost layers of the spore coat. The CotA protein is most probably subject to post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 50 publications
4
136
1
1
Order By: Relevance
“…In only one publication is there electron microscopic evidence of a possible traditional exosporium layer with a defined basal layer and interspace region (185). In this report, as in others, micrographs indicate an external crust-like layer (such as that shown in Fig.…”
Section: Clostridium Difficilementioning
confidence: 48%
See 2 more Smart Citations
“…In only one publication is there electron microscopic evidence of a possible traditional exosporium layer with a defined basal layer and interspace region (185). In this report, as in others, micrographs indicate an external crust-like layer (such as that shown in Fig.…”
Section: Clostridium Difficilementioning
confidence: 48%
“…In this report, as in others, micrographs indicate an external crust-like layer (such as that shown in Fig. 8) or fragments of material adherent to the spore coat in strains of C. difficile (13,174,185,186). Joshi et al also indicated a pronounced variation in spore hydrophobicity among strains, with the more hydrophobic strains possessing a more organized exosporium (173).…”
Section: Clostridium Difficilementioning
confidence: 63%
See 1 more Smart Citation
“…To date, the only protein that has been shown to belong exclusively to the exosporium is the collagen-like BclA1 protein (Pizarro-Guajardo et al, submitted). Other proteins identified to be located at the surface of proteinase K-treated spores (i.e., spores that lack the exosporium layer) are five proteins (i.e., CotA, CotB, CotCB, CotD, and CotE) (37), where only CotA is essential for the assembly of the coat and exosporium of C. difficile spores (38). In this context, this study has made several important contributions to the understanding of the formation of the outermost layers of C. difficile spores.…”
Section: Discussionmentioning
confidence: 99%
“…Algunas especies como C. difficile, poseen una capa más externa llamada exosporium, que presenta proyecciones de filamentos que podrían jugar roles esenciales en la interacción espora-hospedero 39,43,66 y/o en la resistencia de las esporas. Los primeros estudios en factores de resistencia de esporas de C. difficile han identificado dos factores con un rol en la resistencia; estos son: CdeC, el que está involucrado en la resistencia de la espora a etanol, calor y lisozima 65 y CotA, involucrada en la pérdida de la resistencia al calor en un sub-grupo de la población total 67 . Ambos factores alteran el proceso de ensamblaje de las capas externas de las esporas de C. difficile.…”
Section: Factores De Resistencia En La Espora De C Difficileunclassified